Parviz Khalatbari, La explosión demográfica en los países subdesarrollados, Caracas, Universidad Central de Venezuela, 1974. 151 p. - Hernández Millán, Abelardo (El Colegio de México A.C., 1976)
Parviz khalatbari, La explosión demográfica en los países subdesarrollados, Caracas, Universidad Central de Venezuela, 1974.